Policy of Attracting International Students of Northeast Asian Countries - E. K. Belaia; M. A. Kashina (Евразийская интеграция: экономика, право, политика, 2025)
Relevance. Entering the top ten countries in the world in terms of education export is one of the strategic objectives of the Russian state. However, the declared target of 710 thousand foreign students in 2025 is far from being achieved. At the same time, there are countries that are quite successfully solving similar problems. Today, the countries of the Asia-Pacific region are a significant competitor to the countries recognized as leaders in the export of education, so their experience in this area deserves close attention. Aim. Comparative analysis of the experience of recruiting foreign students by Northeast Asian countries — Japan, South Korea and China. Methods. Analysis of secondary sources, sociological and statistical data with an emphasis on foreign sources. Results and conclusions. In all three countries, the key factor in educational migration is the interest of foreign youth in their language and culture. Recruiting foreign students is a government task. This can be seen in such governmental strategies as the ‘Plan to Attract Foreign Students’ in Japan, the ‘Study Korea Project’ in South Korea, and the ‘Study in China Plan’ in China. Recruitment efforts are diversified and built from the top down, from national governments through local authorities to universities and business organizations. The key problem is finding a balance between the quantitative and qualitative parameters of educational migration. Lowering entry requirements for foreign students leads to a decrease in the quality of education. At the same time, since the 2010s, all countries have been taking consistent measures to simplify the employment procedure for foreign graduates in order to solve the problems of national labor markets.